2020
DOI: 10.32479/ijefi.9126
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Entrepreneurial Orientation on Firms Performance: Evidence From Small and Medium Enterprises in Nigeria

Abstract: Entrepreneurship has emerged as promising new solutions to solve societal problems. This study seeks is to analyses how entrepreneurial orientation (EO) i.e. proactiveness, competitive aggressiveness autonomy, innovation, and risk-taking influence firms' performance in Abuja. To fulfil this purpose, survey research design and a theoretical framework were developed depicting the different EOs and firm performance in its context. Sampling technique of simple random was adopted in which only one hundred and ten (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
3
19
0
2
Order By: Relevance
“…In another research considering 0.05 significance level using regression analysis in holistic approach, entrepreneurial mindset have positive effect of on the performance of SMEs (Asenge et al,2018).In some items, there is inconsistence of finding considering identical dimensions. For instance in examining influence of entrepreneurial orientation on firms' performance, Ibrahim and Abu (2020) confirmed that pro-activeness, risktaking and autonomy are positive and significantly related to business performance but competitiveness was positive but insignificant. This implies the contribution of competitiveness is less to the performance of SMEs.…”
Section: Measurements Of Entrepreneurial Competencementioning
confidence: 91%
“…In another research considering 0.05 significance level using regression analysis in holistic approach, entrepreneurial mindset have positive effect of on the performance of SMEs (Asenge et al,2018).In some items, there is inconsistence of finding considering identical dimensions. For instance in examining influence of entrepreneurial orientation on firms' performance, Ibrahim and Abu (2020) confirmed that pro-activeness, risktaking and autonomy are positive and significantly related to business performance but competitiveness was positive but insignificant. This implies the contribution of competitiveness is less to the performance of SMEs.…”
Section: Measurements Of Entrepreneurial Competencementioning
confidence: 91%
“…On the other hand, insufficient competences in a small business could create key issues and difficulties in achieving a high business performance (Pulka, Ramli, Mohamad, 2018). The competences of entrepreneurs have been regarded as crucial factors for success and are research ought to be done in developing countries and similar studies would be repeated to confirm these results (Ibrahim, Abu, 2020).…”
Section: Research Issuementioning
confidence: 96%
“…A deeper analysis of the entrepreneurial orientation dimension in business performance is required (Putnins, Sauka, 2019) and further research is needed (Solikahan, Mohammad, 2019). Ibrahim and Abu (2020) mentioned that parallel research should be undertaken to confirm the results. Further studies are required to establish the nature of the relationship between entrepreneurial orientation and business performance and the aspects that can influence this relationship (Akbar, Bon, Wadood, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The uni-dimensional view EO as a three-factor or composite model made of, innovativeness, proactiveness, and risk-taking of Covin and Slevin ( 1986 ) and contrary to that, Lumpkin and Dess ( 1996 ), viewed EO as having five dimensions where competitive aggressiveness and autonomy have been added to Miller’s assertion of EO, and that not all the five dimensions must manifest to depict SMEs performance, which suggest the need for more studies using the five EO model with mediating and or moderating variables that relate to the internal and external features of SMEs in other forms of businesses and countries to appreciate how each of the variables affect SMEs performance and help reduce confusing descriptive and normative theory building if all the five (5) EO dimensions are not used (e.g. Lumpkin and Dess 2001 ; Wiklund and Shepherd Wiklund and Shepherd 2005 ; Pett and Wolff 2010 ; Mahmood and Hanafi 2013 ; Alembummah 2015 ; Gathenya et al 2011 ; Mason et al 2015 ; Koe Koe 2013 ; Zahra 2008; Arshad et al Arshad et al 2018 ; Rezaei and Ortt 2018 ; Ibrahim and Abu 2020 ). For an enhanced and sustainable performance of SMEs, they need not only financial capital and human capital (i.e.…”
Section: Introductionmentioning
confidence: 99%